Effectiveness of the Alternative Learning System Informal Education Project and the Transfer of Life Skills among ALS Teachers: A Case Study - Manuel E. Caingcoy; Juliet L. Pacursa; Ma. Isidora W. Adajar (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Alternative Learning System (ALS) has been adopted in Philippine basic education, yet there is no academic institution in the region prepares ALS teachers in teaching life skills. ALS teachers graduated from different programs of teacher education for formal education. In response, an extension project was conceptualized and implemented to enhance the teaching capacity and effectiveness of ALS teachers. Case study was conducted to evaluate the effectiveness of the project. It explored the transfer of life skills among ALS teachers. Data were collected from multiple sources. Interview and written responses, and feedbacks were analyzed using thematic narrative analysis. Other data were analyzed using document and descriptive analyses. The project had achieved its objectives and rated best by participants. These indicate that the project was implemented effectively and successfully. ALS teachers have acquired life skills and transferred them to others. Thus, the project has made a difference in the lives of these teachers.